2000
DOI: 10.1007/s000110050584
|View full text |Cite
|
Sign up to set email alerts
|

L-Histidine decarboxylase protein and activity in rat brain microvascular endothelial cells

Abstract: L-Histidine uptaken by rat BMEC was shown to be converted to histamine, suggesting that HDC plays an important role in BBB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…HDC activity has been demonstrated indirectly in aortic segments from rabbits [9] and bovine aortic endothelial cells [10]. However, the only previous evaluation of HDC mRNA in blood vessels has been in rat brain microvascular endothelial cells [5]. Our results are the first to determine the presence of the enzyme mRNA in human vascular endothelial cells and more importantly, in vascular smooth muscle for any species.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…HDC activity has been demonstrated indirectly in aortic segments from rabbits [9] and bovine aortic endothelial cells [10]. However, the only previous evaluation of HDC mRNA in blood vessels has been in rat brain microvascular endothelial cells [5]. Our results are the first to determine the presence of the enzyme mRNA in human vascular endothelial cells and more importantly, in vascular smooth muscle for any species.…”
Section: Discussionmentioning
confidence: 67%
“…In previous studies, HDC mRNA has been detected in various tissues isolated from the rat including the stomach, skin, spleen, liver [4] and cultured rat brain microvascular endothelial cells [5]. The objective of this study was to investigate histamine synthesis capability of human vascular smooth muscle and endothelial cells by determining the presence of HDC mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of only one other publication that has investigated localization of histidine decarboxylase in blood vessels [24]. Yamakami et al [24] detected histidine decarboxylase in rat brain microvascular endothelial cells using immunofluorescence microscopy and nRT-PCR. However, the present study did not detect HDC mRNA in cultured rat aortic endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies [20] using tissue isolated from liver, stomach, and pancreas of fetal rats indicated that most HDC mRNA was located in the liver. Most current research investigating HDC mRNA and protein is directed toward localization and regulation of histidine decarboxylase in stomach [16,21,22] and in brain [23,24]. In these systems, increasing HDC mRNA abundance can lead to apparent HDC activity and increased levels of histamine.…”
Section: Introductionmentioning
confidence: 99%
“…For in vitro studies, rat BMEC were isolated and cultured from rat brains as previously described [1], and subcultured cells were grown on collagen-coated culture flask and slide, and on transwell membrane. Then, L-histidine uptake rate, assay of L-histidine decarboxylase (HDC) activity, immunofluorescence analysis of HDC protein distribution, expression of HDC mRNA by RT-PCR and paracellular transport clearance of fluorescein were performed in rat BMECs [1,2,3]. Values cited in results section are mean AE SEM for n = 5 independent determinations.…”
Section: Methodsmentioning
confidence: 99%